Development of a Method for Detection of Lactic Acid Bacteria Producing Exclusively the l-(+)- Isomer of Lactic Acid - Jehanno, D. (1992)
A method was developed for the detection and isolation, within a population of lactic acid bacteria, of strains producing exclusively the l-(+)- isomer of lactic acid; the visual detection of colonies of these particular strains can be carried out directly on agar plates (50 to 70 colonies per plate). The method is based on an enzymatic stereospecific reaction involving d-(−)-lactate dehydrogenase and linked to a staining reaction; the diffusion area of the d-(−)- isomer stains red around the d-(−)- and the dl-lactic acid-producing colonies, while the colonies producing exclusively l-(+)-lactic acid are detected by the absence of the colored halo. The intensity of staining was increased when cellulose powder and Tween 20 were added to the agar medium.